Racial Discrimination in Langston Hughes' Selected Poems (TRANSFORM: Journal of English Language Teaching and Learning, 2024)
This study aims to interpret racial discrimination in Langston Hughes' poems i.e., I Too Sing America, Negro, and Let America Be America Again. Langston Hughes, as a writer, has faced direct discrimination from white people in his literary work. Many of Langston Hughes's works of poetry tell the story of African Americans who lived as black people and faced discrimination throughout history. Some of his poetry depicts the racial, cultural, and educational discrimination that black people face. The data taken from the poem comes from Langston Hughes' poems including I Too Sing America, Negro, and Let America Be America Again. This study applies the descriptive qualitative method as well as the extrinsic approach. Extrinsic approach, aligned with mimetic and pragmatic approaches. I Too Sing America depicts the oppression of black people through slavery, denial of rights, and inequality. Let America Be America Again depicts a focus on the idea of the American dream and how, for many people, achieving freedom, equality, and happiness, which the dream embodies, is nearly impossible. Negro depicts people of African American descent have the status of slaves. The conclusion is that the author accepts a great deal of discrimination as an African American and rejects differences in skin color status.
Keywords: African American; Racial Discrimination; Langston Hughes